Persepsi Guru Pendidikan Agama Islam terhadap Kepemimpinan Pengawas Madrasah - Hindun; Fathoni (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[THE PERCEPTION OF ISLAMIC EDUCATION TEACHER'S TO THE MADRASAH SUPERVISOR'S LEADERSHIP]. The purpose of writing this paper is to describe the Islamic Education (PAI) teacher's perception of the madrasah supervisor's leadership. The research methodology of this paper is mixed method by combining quantitative methods supported by questionnaires to capture data and qualitative methods with the support of interviews of 20% of the respondent's population. The respondents of this study were PAI at Madrasah Tsanawiyah Negeri and Madrasah Tsanawiyah Private in the North Jakarta Region totaling 32 people. The results of the analysis of the perception of PAI teachers towards the attitude of the madrasah supervisor's leadership in the North Jakarta obtained an average value = 79,916, with a good predicate. Thus, the conclusions of PAI teachers' perceptions of supervisors' leadership attitudes are in a good category.